1980
DOI: 10.1002/asi.4630310208
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of scientific productivity and social change

Abstract: Results in the literature concerning the probability that an author publishes r articles in time t are reexamined, and it is found that a negative binomial distribution fits scientific productivity data (by the chi‐squared goodness‐of‐fit test) better than many other distributions such as geometric, logarithmic, zeta, cumulative advantage, etc. It is shown analytically that the negative binomial distribution describes a pattern of scientific productivity under the “success‐breeds‐success” condition in a wide v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Lack of zero-frequency data causes no problem in applying Equation (3). Only the first point (belonging to s = 0) will be missing, but this raises no difficulties in using either the test or the parameter estimation.…”
Section: Its Expectation Ismentioning
confidence: 96%
See 2 more Smart Citations
“…Lack of zero-frequency data causes no problem in applying Equation (3). Only the first point (belonging to s = 0) will be missing, but this raises no difficulties in using either the test or the parameter estimation.…”
Section: Its Expectation Ismentioning
confidence: 96%
“…A considerable part of this literature proposed and tested various theoretical models of the productivity distribution. Several of them were comparatively assessed by Rao [3]. One may think, therefore, that any more attempt to argue for or against any of these distributions is like chewing old bones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rao (1980), by examining the distribution is that it cannot fit real data, or as stressed by tribution of scientific productivity, showed that the nega- Sichel (1992), ''the Waring and Yule distributions have tive binomial provided a remarkably better fit than the linear tails in a double logarithmic grid, and hence they Price model. However, when applied to the journal proare unsuitable for representing the upper tails of most ductivity in economics (Rao, 1990), a poor fit has been observed bibliometric size-frequency data,'' (p. 7) since observed.…”
Section: Simon-yule Distributionmentioning
confidence: 97%
“…[The earliest example of a negative binomial distribution (NBD) being fitted to what would now be called scientometric data seems to be Neelameghan et al (1969), who termed it a modified Poisson distribution.] The reasonable success of the NBD was extensively reported by Ravichandra Rao (1980Rao ( , 1982, although alternatives were suggested, for example, by Hindle and Worthington (1980). The shortcomings of the NBD are particularly revealed by its failure to describe many of the classic examples of informetric data sets which have notoriously long tails.…”
Section: Introductionmentioning
confidence: 94%